Menthyl esterification allows chiral resolution for the synthesis of artificial glutamate analogs - Morokuma, Kenji; Tsukamoto, Shuntaro; Mori, Kyosuke; Miyako, Kei; Sakai, Ryuichi; Irie, Raku; Oikawa, Masato (Beilstein Journal of Organic Chemistry, 2021)
Herein, we report the enantiospecific synthesis of two artificial glutamate analogs designed based on IKM-159, an antagonist selective to the AMPA-type ionotropic glutamate receptor. The synthesis features the chiral resolution of the carboxylic acid intermediate by the esterification with ʟ-menthol, followed by a configurational analysis by NMR, conformational calculation, and X-ray crystallography. A mice in vivo assay showed that (2R)-MC-27, with a six-membered oxacycle, is neuroactive, whereas the (2S)-counterpart is inactive. It was also found that TKM-38, with an eight-membered azacycle, is neuronally inactive, showing that the activity is controlled by the ring C.
Keywords: chiral resolution; configurational analysis; glutamate; metathesis; neuroactivity

(untitled) - Riedel, G.; Platt, B.; Micheau, J. (Behav. Brain Res., 2003)

(untitled) - Gill, M. B.; Frausto, S.; Ikoma, M.; Sasaki, M.; Oikawa, M.; Sakai, R.; Swanson, G. T. (Br. J. Pharmacol., 2010)

(untitled) - Juknaitė, L.; Sugamata, Y.; Tokiwa, K.; Ishikawa, Y.; Takamizawa, S.; Eng, A.; Sakai, R.; Pickering, D. S.; Frydenvang, K.; Swanson, G. T.; Kastrup, J. S.; Oikawa, M. (J. Med. Chem., 2013)

(untitled) - Tsukamoto, S.; Itagaki, H.; Morokuma, K.; Miyako, K.; Ishikawa, Y.; Sakai, R.; Oikawa, M. (Heterocycles, 2020)

(untitled) - Chiba, M.; Fujimoto, C.; Sakai, R.; Oikawa, M. (Bioorg. Med. Chem. Lett., 2015)

(untitled) - Oikawa, M.; Ikoma, M.; Sasaki, M.; Gill, M. B.; Swanson, G. T.; Shimamoto, K.; Sakai, R. (Eur. J. Org. Chem., 2009)

(untitled) - Oikawa, M.; Ikoma, M.; Sasaki, M.; Gill, M. B.; Swanson, G. T.; Shimamoto, K.; Sakai, R. (Bioorg. Med. Chem., 2010)

(untitled) - Ikoma, M.; Oikawa, M.; Gill, M. B.; Swanson, G. T.; Sakai, R.; Shimamoto, K.; Sasaki, M. (Eur. J. Org. Chem., 2008)

(untitled) - Shiina, I.; Kubota, M.; Oshiumi, H.; Hashizume, M. (J. Org. Chem., 2004)

CONFLEX, Version 5 (Conflex Corporation, 2004)

(untitled) - Goto, H.; Ōsawa, E. (J. Am. Chem. Soc., 1989)

(untitled) - Gotō, H.; Ōsawa, E. (J. Chem. Soc., Perkin Trans. 2, 1993)

(untitled) - Pamuła, M.; Nissinen, M.; Helttunen, K. (Chem. – Eur. J., 2020)

WO Patent - Zhan, Z.-Y. (Ruthenium complex ligand, ruthenium complex, carried ruthenium complex catalyst and the preparing methods and the use thereof, 2007)

(untitled) - Bracegirdle, S.; Anderson, E. A. (Chem. Soc. Rev., 2010)

(untitled) - Kleinke, A. S.; Webb, D.; Jamison, T. F. (Tetrahedron, 2012)

(untitled) - Flynn, D. L.; Zelle, R. E.; Grieco, P. A. (J. Org. Chem., 1983)

(untitled) - Kraus, G. A.; Taschner, M. J. (J. Org. Chem., 1980)

(untitled) - Bal, B. S.; Childers, W. E., Jr; Pinnick, H. W. (Tetrahedron, 1981)

(untitled) - Dalcanale, E.; Montanari, F. (J. Org. Chem., 1986)

(untitled) - Uesugi, S.-i.; Watanabe, T.; Imaizumi, T.; Ota, Y.; Yoshida, K.; Ebisu, H.; Chinen, T.; Nagumo, Y.; Shibuya, M.; Kanoh, N.; Usui, T.; Iwabuchi, Y. (J. Org. Chem., 2015)

(untitled) - Yabuuchi, T.; Kusumi, T. (J. Org. Chem., 2000)

(untitled) - Pan, G.; Xu, Z.; Guo, Z.; Hindra; Ma, M.; Yang, D.; Zhou, H.; Gansemans, Y.; Zhu, X.; Huang, Y.; Zhao, L.-X.; Jiang, Y.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Chiba, M.; Ishikawa, Y.; Sakai, R.; Oikawa, M. (ACS Comb. Sci., 2016)

(untitled) - Badorrey, R.; Cativiela, C.; Diaz-de-Villegas, M. D.; Gálvez, J. (Tetrahedron: Asymmetry, 1995)

(untitled) - Tverezovsky, V. V.; Baird, M. S.; Bolesov, I. G. (Tetrahedron, 1997)

(untitled) - Sakai, R.; Kamiya, H.; Murata, M.; Shimamoto, K. (J. Am. Chem. Soc., 1997)

(untitled) - Murakami, S.; Takemoto, T.; Shimizu, Z. (Yakugaku Zasshi, 1953)

(untitled) - Zhang, J.; Yu, P.; Li, S.-Y.; Sun, H.; Xiang, S.-H.; Wang, J.; Houk, K. N.; Tan, B. (Science, 2018)

(untitled) - Sakai, R.; Swanson, G. T.; Shimamoto, K.; Green, T.; Contractor, A.; Ghetti, A.; Tamura-Horikawa, Y.; Oiwa, C.; Kamiya, H. (J. Pharmacol. Exp. Ther., 2001)